MR-Guided Microwave Ablation for Lung Malignant Tumor: A Single Center Prospective Study - Lin, Ruixiang; Fang, Yan; Chen, Jin; Lin, QingFeng; Chen, Jian; Yan, Yuan; Chen, Jie; Lin, Zhengyu (Frontiers in Oncology, 2022)
Abstract Objectives: To prospectively investigate the feasibility and efficacy of MRI-guided MWA for lung malignant tumor in our single center. Materials and Methods: 22 patients (mean age, 56.86±13.05[23–73]years) with 23 malignant lung tumors were enrolled in the study. 21 patients had a single lesion and 1 patient had 2 lesions in the ipsilateral lung. The average maximum diameter of the lesion was 1.26±0.65 (0.50-2.58)cm. Percutaneous MWA was guided by 1.5T MRI scanner using a MR-compatible microwave antenna to the target the lung lesions and ablation area was monitored intraoperatively by using a shielded MR-compatible microwave device and then follow-up. Results: All patients were successfully treated under MR-guided MWA for lung tumors. Average operation time was 72.21±24.99 (36–158) mins. T2WI signal intensity of the lesion gradually decreased over the course of MWA. The center of the ablated zones showed a short T1 and short T2 signals with the ring-like of long T1 and long T2 signals surrounded after immediately evaluation. No serious complications occurred. The average follow-up period was 12.89±4.33 (2.0-19.6）months. Local recurrence occurred in one patient, representing a technical efficacy of 95.5% (21/22). Conclusion: Magnetic resonance-guided microwave ablation for lung malignant tumor was feasible and demonstrated unique advantages in efficacy evaluation.